2004
DOI: 10.4314/sajas.v34i1.4039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a mixture of herbal essential oils or á-tocopheryl acetate on performance parameters and oxidation of body lipid in broilers

Abstract: Performance parameters and oxidation of body lipids of broiler chickens were investigated when their diet was supplemented with a commercial preparation of essential oils (Apacox) derived from selected herbs. One hundred and twenty day-old Cobb-500 female chicks were divided into four groups with three replicates each. One group received the basal diet, the control. The three experimental diets consisted of the basal diet to which either 200 mg α-tocopheryl acetate/kg (Toc200 group), Apacox at 0.5 g/kg (Apa0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
76
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 40 publications
14
76
1
1
Order By: Relevance
“…The results of the present study agree with previous observation that indicated herbs, plant extracts, essential oil and/or the main components of the essential oil that did not affect body weight gain, feed intake or feed efficiency in broilers (Botsoglou et al, 2004;Bampidis et al, 2006;Cross et al, 2007). Ocak et al (2008) found that body weight gain, feed intake or feed conversion ratio were not significantly affected by dietary supplementation of thyme leaves.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study agree with previous observation that indicated herbs, plant extracts, essential oil and/or the main components of the essential oil that did not affect body weight gain, feed intake or feed efficiency in broilers (Botsoglou et al, 2004;Bampidis et al, 2006;Cross et al, 2007). Ocak et al (2008) found that body weight gain, feed intake or feed conversion ratio were not significantly affected by dietary supplementation of thyme leaves.…”
Section: Discussionsupporting
confidence: 92%
“…Essential oils derived from herbs have antimicrobial properties (Faleiro et al, 2003). It has been reported that herb extracts have antibacterial characteristics, antioxidant activity, and enhance digestibility by stimulating endogenous enzyme activity and facilitating nitrogen absorption (Azaz et al, 2002;Botsoglou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of GP effects on broilers feed intake, weight OPEN ACCESS gain and feed conversion ratio observed in this study is in agreement with previous observations that indicated that herbs, plant extracts, essential oil and/or the main components of the essential oil that did not affect body weight gain, feed intake or feed efficiency in broilers [6,10,[16][17][18][19][20][21][22]. Lewis et al (2003) [7] showed that addition of plant extracts to broilers' diet has some effects on performance and microbial activity of intestinal tract but, none of them were significant.…”
Section: Weight Gainsupporting
confidence: 92%
“…Highest final weight (290.2g) was observed in quails fed 3% PLMGPD followed by quails fed diet 4 with 280.1g, the lowest weight was recorded in quails fed diet 1 with 259.3g. This observation agrees with the views of Dieumou et al (2012) on the effect feeding ginger and garlic on the performance of broilers and Alagbe, J.O (2017) on the dietary inclusion of P. longifolia leaf meal as phytobiotic compared with antibiotics on broiler performance and contrary to the reports of Amouzmehr et al (2013); Botsoglu et al (2004); Kamal and Abo (2012) and Safa et al (2012). The higher weight recorded could be as a result of the synergistic combination of PLM + GLPD mixture which help to reduce disease pressure on the animals, thereby increasing the opportunity of the flock to achieve better FCR and improved performance.…”
Section: Discussionsupporting
confidence: 90%